A critical review of the Motor-Free Visual Perception Test—fourth edition (MVPT-4). Issue 2 (3rd April 2018) - Brown, Ted; Peres, Lisa
ABSTRACT: The Motor-Free Visual Perception Test—fourth edition (MVPT-4) is a revised version of the Motor-Free Visual Perception Test—third edition . The MVPT-4 is used to assess the visual-perceptual ability of individuals aged 4.0 through 80+ years via a series of visual-perceptual tasks that do not require a motor response. Test norms were derived from a normative sample closely matching the United States population. Reliability and validity of the MVPT-4 was described and a critique of the MVPT-4's psychometric properties is presented. The MVPT-4 was critiqued based on the "Quality Criteria for Health Status Questionnaires" (QCHSQ) and the "Consensus-based Standards for the Selection of Health Measurement Instruments" (COSMIN). According to the QCHSQ, the MVPT-4 exhibits good levels of content validity, construct validity, and interpretability, although information about its reliability, criterion validity, responsiveness, and floor and ceiling effects are poor. According to the COSMIN, the MVPT-4 demonstrated poor measurement error, structural validity, cross-cultural validity, criterion validity, responsiveness, and generalizability; fair internal consistency, reliability, hypothesis testing, and interpretability; and excellent content validity. Practical implications of the use of the MVPT-4 in clinical practice and research are outlined. Further research is needed to determine the cross-cultural generalizability, predictive validity, responsiveness, clinical utility, and dimensionality of the MVPT-4.